Delayed metastasis in patients with intraocular retinoblastoma: A review of three cases. Issue 4 (July 2021) - Vempuluru, Vijitha S; Jakati, Saumya; Kaliki, Swathi
Purpose: To discuss the clinical presentation, management, and outcome of delayed metastasis in retinoblastoma (RB). Methods: Retrospective case series of three patients. Results: Mean age at diagnosis of RB was 29 months (median, 28 months; range, 11–48 months). All were males with non-familial bilateral intraocular RB. Primary treatment for RB included intravenous chemotherapy in all three cases. Secondary treatment included transpupillary thermotherapy/cryotherapy ( n  = 6 eyes), periocular chemotherapy ( n  = 2 eyes), intravitreal chemotherapy ( n  = 1 eye), intra-arterial chemotherapy ( n  = 1 eye), external beam radiotherapy (EBRT; n  = 2 eyes), and enucleation ( n  = 2 eyes). Primary tumor regression was achieved in all cases and remained status quo at the time of diagnosis of distant metastasis. Two patients developed bone metastasis (ulna; tibia) and one developed soft tissue metastasis (temporal fossa) over a mean follow-up period of 6 years (median, 7 years; range, 5–8 years) from diagnosis of RB. Mean age of detection of metastatic disease was 8 years (median, 8 years; range, 7–9 years). All the lesions were solitary and the diagnosis of metastatic retinoblastoma was confirmed by tissue biopsy. Metastatic disease was treated with surgical excision ( n  = 1), chemotherapy ( n  = 2), and EBRT ( n  = 2). All patients are alive, with two patients free of disease over a mean follow-up period of 23 months (median, 23 months; range, 12–33 months); and 1 in remission 7 months after completion of EBRT. Conclusion: Long-term follow-up of RB cases is mandatory. In spite of intraocular tumor regression, metastasis can still occur many years after treatment of RB.